INTRAORAL VERRUCA VULGARIS - Sen, Suman; Sheuli Sen, (Journal of Ayub Medical College Abbottabad, 2021)
A 58-year-old male visited to the Department of Oral medicine and radiology in Indraprastha Dental Hospital (India) with chief complaints of a white lesion in the left buccal mucosa since last 4 month which was gradually increasing in size. His past medical history was non-contributory and similar lesions are not present among his other family members. On intraoral examination, a solitary proliferative verrucous growth over the left buccal mucosa was noted. The lesion was exophytic and sessile in nature, approximately 1Ã—1 cm in size, with well-defined margins. Surface of the lesion was irregular with finger-like projections. The colour was white, non-tender and soft in consistency [Figure-1] Multiple differential diagnosis was given as squamous papilloma, condylomata accuminatum, keratoacanthoma, exophytic verrucous carcinoma, focal epithelial hyperplasia, verruciform xanthoma. So, a biopsy was decided. The lesion was excised completely under local anaesthesia and sutured. [Figure-2] The excised biopsy sample was sent for histopathological examination. [Figure3] Under hemotoxin and eosin staining showed superficial layers of the epithelium demonstrate koilocytotic changes. There is polypoid mass with an epithelium displaying acanthosis, and papillomatosis. There was proliferation of hyperkeratotic stratified squamous epithelium arranged into pointed projections with connective tissue cores. Elongated rete ridges tend to converge toward the center of the lesion, producing a '˜cupping' effect. This leads to final diagnosis of Verruca Vulgaris of buccal mucosa. Oral verruca vulgaris is caused by human papillomavirus (HPV) mostly by type 6 and 11 infection.1 Verruca vulgaris most frequently occurs on the fingers, toes, soles, and dorsal surfaces of hands and is mostly asymptomatic. It's rarely seen in oral cavity. Viral products stimulate cell growth in the basal layer that leads to formation of a wart which has malignant potential due HPV infection.2 Varieties of verrucous lesions affect oral mucosa which can be reactive. It commonly observed skin growths in childhood with equal gender predilection. Intraoral warts can occur at any age with equal incidence in both genders but are most commonly seen in the third to fifth decade. Medication that can be advised are cimetidine, levamisole, retinoids, immunomodulator. It can also be removed by surgical excision or laser.3